Physico-chemical changes in developed probiotic chicken meat spread fermented with Lactobacillus acidophilus and malted millet flour - Namrata Agrawal; Pradeep Kumar Singh; Gauri Jairath; Md Faruque Ahmad; António Raposo; Anjum Khanam; Sehad N. Alarifi; Heesup Han; Neha Thakur (Applied Food Research)
This study was envisaged to develop a probiotic chicken meat spread fermented with Lactobacillus acidophilus (Lactic acid bacteria-LAB) and malted sorghum flour as a substrate and evaluation of its quality. Chicken meat spread was prepared by incorporating malted sorghum flour at 0, 2, 4 and 6 % (w/w) levels as a substrate in the product's formulation, along with Lactobacillus acidophilus at a concentration of 1 million cfu/g of the product. The product prepared with different formulations i.e. C (meat spread only), C1 (meat spread with 0 % malted sorghum flour + LAB), T1 (meat spread with 2 % malted sorghum flour + LAB), T2 (meat spread with 4 % malted sorghum flour + LAB) and T3 (meat spread with 6 % malted sorghum flour + LAB) were assessed for fresh product study and the storage stability at refrigeration temperature for 16 days when the physico-chemical parameters were analyzed. The fresh product study revealed significantly (p ≤ 0.05) higher moisture content in the T3 group. However, lower protein, ether extract, and ash content in T2 and T3 samples compared with the control, whereas a higher emulsion stability and cooking yield in the T2 group were observed when compared with the control. Free fatty acid, thiobarbituric acid, and titratable acidity values significantly (p ≤ 0.05) increased for the fermented samples in comparison to the control, and the same trend continued during the entire storage period. This study showcases the potential of using malted sorghum flour and Lactobacillus acidophilus to enhance the functional properties of chicken meat spreads, making them more nutritious and appealing to health-conscious consumers. Future research should focus on optimizing ingredient proportions and exploring alternative substrates to further improve these functional meat products.